Phone Home Automation - Ola Husam Saeed; Ruba Ghaleb Abu Baker (My University, 2011)
Home automation is simplified all about control electrical, electronics, security and entertainment at a touch of a finger, all working from remote control.Home automation is becoming more and more popular around the world and is becoming a common practice. The process of home automation works by making everything in the house automatically controlled using technology to control and do the jobs that we would normally do manually.We are coming up with one of such interesting systems by which we can access even our bedroom electronic devices even from the most far off places in the world, provided the network under use has good range everywhere.

Home automation is simplified all about control electrical, electronics, security and entertainment at a touch of a finger, all working from remote control. Home automation is becoming more and more popular around the world and is becoming a common practice. The process of home automation works by making everything in the house automatically controlled using technology to control and do the jobs that we would normally do manually. We are coming up with one of such interesting systems by which we can access even our bedroom electronic devices even from the most far off places in the world, provided the network under use has good range everywhere.
Phone Home Automation